If-- [videorecording (DVD)] - Anderson, Lindsay, 1923-1994; McDowell, Malcolm, 1943-; Wood, David, 1944-; Warwick, Richard, 1945-1997 (Criterion collection, 2007)
In late 1960s England, Mick Travis and his school chums trump authority at every turn at their boarding school. He finally emerges as violent savior against the draconian games of one-upmanship played by both students and the powers that be.